Experiências formativas: caminhos percorridos na interface entre a terapia ocupacional e a comunicação alternativa e ampliada em contexto escolar - Borges, Bianca Costa (Universidade Federal de São Carlos, 2021)
The literature indicates that people with complex communication needs due to distinct health conditions, congenital or acquired, can benefit from Augmentative and Alternative Communication (AAC). Emphasizing the implementation of AAC resources in the school context, the figure of the teacher appears as a communication partner, essential in the process of systems use. Besides that, AAC at the school enable the creation of a bridge that connects education and health professionals, taking in consideration the person multiple life contexts, and the need to integrate knowledges so that the process of communication trough ACC be successful. The Federal Council of Physiotherapy and Occupational Therapy (COFFITO) recognizes occupational therapy in the school context as one of the profession specialties, highlighting Assistive Technology and AAC as one of the areas of expertise occupational therapists must know to act in this context. Therefore, occupational therapists are set as professionals capable of implementing AAC resources in the school context. Starting from these notes, this work has the objective to describe my undergraduate tracked route in Assistive Technology and AAC fields, through three products presentation: an experience and participation report in the extension project of alternative communication on the assistance to the disable child, developed at an special education institution of São Carlos-SP; as a second product, a scientific initiation research literature review about partner communication training in the school context, and the third product, an abstract submission of this research with an specific cutout focusing on the interface between health professionals and teachers at school setting. This route inside occupational therapy emphasizing AAC was essential to my occupational therapy training, considering people uniqueness and autonomy, as well the need to work an occupation so essential in human life as communication is.
Training experiences: traveled paths on the interface between occupational therapy and augmentative and alternative communication in the school context
Keywords: Tecnologia Assistiva; Comunicação alternativa; Terapia Ocupacional; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL